Factors Affecting the Development of Cashless Economy in Vietnam - Binh, Nguyen Van; Mai, Pham Quynh; Huy, Luu Quang (Business and Economic Research, 2024)
Cashless economy is a common development trend of countries. It reflects the development level of a country as well as ensuring financial transparency. In Vietnam, cashless payment has gradually become familiar to most people and businesses in society. By using traditional research methods, such as synthesizing information, combining with practical observations, the authors would like to analyze and clarify the factors affecting the development of a cashless economy in Vietnam as well as propose some solutions to promote the formation of a cashless economy in Vietnam